2022
DOI: 10.1108/jbim-08-2021-0391
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive marketing capabilities, market orientation, and international performance: the moderation effect of competitive intensity

Abstract: Purpose It is well established in marketing literature that international performance is positively affected by marketing capabilities, whether static or dynamic. However, recent theoretical development proposed adaptive marketing capabilities (AMC) as a set of capabilities able to close the marketing gap. Given the relative newness of this construct, empirical studies are still scarce. Therefore, drawing from a resource-based view perspective, this study aims to analyse the relationships among market orientat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 103 publications
0
17
0
Order By: Relevance
“…This result is supported by the study that showed market access conditions relative to those faced by competitors rather than CO per se significantly influence export performance (Chen et al , 2015; Fugazza and McLaren, 2014). However, other contradictory data indicate a negative or nonexistent relationship between competition orientation and performance (Al-Hakimi et al , 2022; Gaur et al , 2011; Reimann et al , 2022). As a result, for service firms, focusing on varying customer needs does not affect export performance because of standardization requirements and the improvement necessity of the employees and firm processes.…”
Section: Discussionmentioning
confidence: 99%
“…This result is supported by the study that showed market access conditions relative to those faced by competitors rather than CO per se significantly influence export performance (Chen et al , 2015; Fugazza and McLaren, 2014). However, other contradictory data indicate a negative or nonexistent relationship between competition orientation and performance (Al-Hakimi et al , 2022; Gaur et al , 2011; Reimann et al , 2022). As a result, for service firms, focusing on varying customer needs does not affect export performance because of standardization requirements and the improvement necessity of the employees and firm processes.…”
Section: Discussionmentioning
confidence: 99%
“…According to Anning-Dorson (2018b) and Groza et al (2021), highly innovative firms normally adopt the latest technological advances to improve their operations and customer relationships. Previous studies have established that the focus of market orientation is to fulfil customer needs in customer-centric or market-driven strategies (Andreou et al, 2020;Anees-ur-Rehman and Johnston, 2019;Masa'deh et al, 2018;Reimann et al, 2023). These insights drive the theoretical basis for correlation among market orientation, brand orientation, bank innovativeness and bank performance.…”
Section: Rq2mentioning
confidence: 97%
“…Therefore, being market-oriented will help banks respond to customer needs and maintain relationships with customers to achieve superior bank performance (Nourallah et al, 2021). In addition, market development demonstrates that market orientation is associated with firm performance (Chahal et al, 2016;Nassani and Aldakhil, 2023;Prifti and Alimehmeti, 2017;Reimann et al, 2023). Taken together, the following hypotheses are formulated:…”
Section: Bank Performancementioning
confidence: 99%
“…When reviewing the extant IMC articles, the most frequently used antecedents could be split into two categories: (1) marketing theory rooted concepts (e.g. market orientation (Reimann et al, 2022), segmentation and targeting (Cortez and Hidalgo, 2022)) and ( 2) international business related phenomena (e.g. international vision (Weerawardena et al, 2015), increased number of foreign markets (Ledesma-Chaves et al, 2020), firm's cultural intelligence (Hazzam and Wilkins, 2022)).…”
Section: Antecedents To the Idmcmentioning
confidence: 99%